Leadership and Intention to Leave Among Public Health Sector Physicians in Cyprus: A National Cross-Sectional Study - Gregoriou, Ioanna; Economidou, Eleftheria Ch; Avraam, Demetris; Soteriades, Elpidoforos Soterakis; Papastavrou, Evridiki; Charalambous, Andreas; Stylianides, Antonis; Merkouris, Anastasios (My University, 2023)
Physician shortage is a major concern in many health care systems globally, while healthcare leadership constitutes one of the most vital factors within human resource management. Our study examined the relationship between managers' leadership styles and physicians' intent to leave their current position. In this cross-sectional national survey, questionnaires were distributed to all physicians working in the public health sector of Cyprus. Most demographic characteristics evaluated by chi-square or Mann-Whitney test, were statistically significantly different between those who intended to leave their job and those who did not. The results of our study demonstrated that transformational leadership has a positive influence on retention of physicians in public hospitals, while non leadership infers a negative influence. Developing leadership skills in physician supervisors is of a great importance for organizations to make a large impact on health professionals' retention and overall performance.
Keywords: Cyprus; Intention to leave; Leadership; Physicians